Effort Incentives and On-the-Job Search: An Alternative Role for Efficiency Wages in Employment Contracts - Daniel Herbold (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We study an infinitely repeated principal-agent relationship with on-the-job search. On-the-job search is modeled as a dimension of the agent's effort vector that has no effect on output, but raises his future outside option. The agent's incentives to search are increasing in the degree to which a higher outside option improves his gains from trade. Search also increases the agent's cost of effort thus generating an effort-substitution problem between work and search effort. We show that the principal can mute search incentives by offering an e fficiency wage contract. Due to effort substitution, e fficiency wages increase the agent's work effort incentives for a given bonus scheme. Thus, effi ciency wages serve as a complement rather than as a substitute to piece rates. Our results provide a new rationale for the use of effi ciency wages as an incentive device and hence greatly extend the set of environments in which e fficiency wages are predicted to be useful as an incentive device. Our findings thus also contribute to the explanation of empirically observed inter-industry variation in the size and composition of worker compensation.
Keywords: C73; D86; J33; 330